P016 Parent/carer intended non- adherence to their child's medication regimen. Issue 7 (19th June 2019) - Aston, Jeff; Wilson, Keith; Terry, David
Abstract : Aim: To identify intended non-adherence reported by parents/carers of children/young people taking long-term medication. Methods: A 10 question postal survey was sent to 180 parents of patients receiving medication via homecare at a tertiary paediatric hospital with a single repeat mailing. Demographic details collected were age, current prescribed medication and duration. Participants were asked about changes that they had made to their child's medication without consulting a healthcare professional. They were asked about delaying/not starting new medication, compliance with medication instructions, with-holding medication, altering the dose of medication, altering medication taking to fit in with daily life and strategies to aid administering medication. The data were analysed using SPSS version 23 and NVivo version 11. Results: The response rate was 32/180 (17.8%). The mean age of respondents was 8.4 years (range 0.83 to 17 years). One hundred and fifty-eight medications were prescribed with a mean of 5 medications per patient (range 1 to 15). In total, 16/32 (50%) respondents had made changes to their child's medication. The most common change (9/32, 28.1%) was adjusting the medication regimen to fit around daily life followed by delaying initiating a new medication (7/32, 20.6%). No respondents indicated that they had not started a new prescribed medication. Six (17.6%) respondents indicated that they had not followed the medication instructions. Four (11.8%) respondents advised that they had withheld their child's medication. Four (11.8%) respondents communicated that they had given a higher than prescribed dose and four (11.8%) a lower dose. Three (8.8%) respondents adjusted how they gave their child's medication to aid administration. Conclusion: Half of respondents made changes to their child's medication without consultation with a healthcare professional. Commonly changes were made to fit around daily life. The decision to prescribe medication should be undertaken in partnership with patients. 1 Adherence to medication in long-term paediatric conditions is particularly complex requiring parents to balance the daily needs of their child taking medication with everyday life. 2 Strategies to support medication adherence include self-management programmes, simplified dosing regimens and pharmacist led medication reviews. 3 Parents/carers may benefit from a structured medication review for their child although further research is required to determine the effectiveness of such an intervention. This study has identified parent practices that could be included in such a review. References: National Institute for Health and Care Excellence. Medicines optimisation: the safe and effective use of medicines to enable the best possible outcomes . London: NICE. 2015. Santer M, Ring N, Yardley L, et al. Treatment non-adherence in paediatric long-term medical conditions: systematic review and synthesis of qualitative studies of caregivers' views. BMC Pediatrics 2014;14:63. Ryan R, Santesso N, Lowe D, et al. Interventions to improve safe and effective medicines use by consumers: an overview of systematic reviews. Cochrane Database of Systematic Reviews 2014, Issue 4. Art. No.: CD007768.